2014
DOI: 10.1111/bjh.12714
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, management and prognosis of multifocal primary bone lymphoma: a retrospective study of the international extranodal lymphoma study group (the IELSG 14 study)

Abstract: Summary'Multifocal bone lymphoma' or 'polyostotic lymphoma' is a neoplasm with exclusive multifocal involvement of the skeleton, without affecting lymph nodes or other soft tissues. Knowledge on this uncommon condition is limited because the related literature is sparse and fragmentary. We reviewed cases of multifocal bone diffuse large B-cell lymphoma (MB-DLBCL) registered in a clinico-pathological database of the International Extranodal Lymphoma Study Group that includes 499 cases of bone lymphoma. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 24 publications
6
46
1
5
Order By: Relevance
“…Several retrospective studies reported PB lymphomas separately and suggested that these topographic variants may have a seemingly favorable prognostic particularly when combining chemotherapy and radiation therapy (Table 2). [7,11,13,27] However, these studies report heterogeneous data and while DLBCL is the most frequently described histological subtype, other lymphomas are reported including follicular or anaplastic types. In contrast to most studies (Table 2), we excluded from our analysis non-DLBCL lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies reported PB lymphomas separately and suggested that these topographic variants may have a seemingly favorable prognostic particularly when combining chemotherapy and radiation therapy (Table 2). [7,11,13,27] However, these studies report heterogeneous data and while DLBCL is the most frequently described histological subtype, other lymphomas are reported including follicular or anaplastic types. In contrast to most studies (Table 2), we excluded from our analysis non-DLBCL lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the IELSG-14 study, the addition of radiotherapy following chemotherapy, or the use of larger radiation fields and doses, were not associated with an improved outcome in patients treated with chemoradiotherapy (9). Although previous studies have obtained contradicting results, chemoradiotherapy is likely to be superior to single modality therapy, which may be advantageous for localized unifocal bulky sites of disease, which allows a shorter chemotherapy course (1,30,35), or for multifocal disease in relapsing cases (36). Anthracycline-containing chemotherapy has become the standard therapy of DLBCL, while numerous studies have demonstrated increased long term remission rates with the incorporation of rituximab (33,(37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the five-year OS and PFS rates of multifocal bone DLBCL, such as this case, were reported to be 36.7-74% and 13.4-34%, respectively (1,2). Several studies have identified predictors of the prognosis of PBL.…”
Section: Case Reportmentioning
confidence: 77%
“…It accounts for 5% of extranodal lymphomas (1)(2)(3)(4)(5)(6), less than 1% of all non-Hodgkin's lymphomas (3,6,7), and 3% of all primary malignant bone tumors (2,5,8). Patients with rheumatoid arthritis (RA) tend to develop lymphoproliferative disorders (LPD) at a frequency of 2.0-5.5 times higher than that in the general population.…”
Section: Introductionmentioning
confidence: 99%